Assessment of toxic effect of centella asiatica extract and its application as natural preservative in fresh-cut mango, pear and cabbage - Suzita Ramli (Tanjung Malim, 2021)
Assessment of toxic effect of centella asiatica extract and its application as natural preservative in fresh-cut mango, pear and cabbage by Suzita Ramli